The association between tuberculosis and the development of insulin resistance in adults with pulmonary tuberculosis in the Western Sub-District of the Cape Metropole region - Philips, Lauren (Stellenbosch : Stellenbosch University, 2015)
Thesis (MNutr)--Stellenbosch University, 2015.